PENGARUH PROMOSI JABATAN TERHADAP KEPUASAN KERJA KARYAWAN DI KANTOR WILAYAH DIRJEN PAJAK (DJP) SUMSEL DAN KEPULAUAN BANGKA BELITUNG - RIZKY ANDINI; BADIA PERIZADE; AGUSTINA HANAFI (JEMBATAN, 2013)
ABSTRACT Purpose of this research is to know and analyze the effect of promotion on Job Satisfaction of employees in Kantor Wilayah Dirjen Pajak (DJP) Sumsel and Kepulauan Bangka Belitung. Sampling using census technic with a total population (employees) Kantor Wilayah Dirjen Pajak (DJP) Sumsel and Kepulauan Bangka Belitung totaling 91 employees. Respondents derived from distribution of questionnaires by 55 respondents. Variabel measurement in this research used Questionnaries Linkert Scale and the type of collected data is primary data. The collected data are treated using simple regression analysis. The result showed that simple linear regression equation was obtained to Y = 27.412 + 0.487 X and t value 10,199 > t table 1,673. Based on these result indicated that job promotion has a positive and significant effect on job satisfaction of employees in Kantor Wilayah Dirjen Pajak (DJP) Sumsel and Kepulauan Bangka Belitung. Promotion policy can be maintained for a defined good promotional companies make employees feel satisfaction in their work and enhance their knowledge and job experience of the employees.